Impact of Teacher-Led Reproductive Health Education on Knowledge Among Vocational High School Students - Puriastuti, Alifia Candra; Novembriani, Rizqie Putri; Hasanah, Winny Kirana; Suprobo, Nina Rini (Jurnal Kesehatan Vokasional, 2026)
Background: Adolescent reproductive health remains a major concern in Indonesia due to the increasing prevalence of risky sexual behavior and low reproductive health literacy among students. Teachers play a strategic role in delivering comprehensive reproductive health education (RHE) within the school environment.Objective: This study aimed to assess changes in students’ knowledge before and after the intervention.Methods: A pre-experimental design using a one-group pretest–posttest approach was used, involving 139 tenth-grade students from State Vocational High School 2 and 3 Malang. Data were collected using pretest and posttest questionnaires and analyzed with a paired t-test.Results: The results showed a significant increase in students’ knowledge after receiving RHE from teachers, both at First VHS (p < 0.001) and Second VHS (p < 0.001). Most students (68.3%) showed improvement, and more than half stated that RHE is essential to be taught in schools.Conclusion: In conclusion, RHE delivered by teachers is effective in enhancing students’ knowledge. Therefore, strengthening teachers’ capacity and integrating RHE into the school curriculum are crucial strategies to foster healthy, knowledgeable, and responsible adolescents.